The complexities of guide dog partnerships: why some go wrong and the impact of a failed relationship on the owner - Whelan, Chantelle (2017)
Guide dogs assist visually impaired individuals with their mobility, as well as conferring social and psychological benefits to the owner. Whilst a guide dog typically works for five to six years, approximately 15-20% are retired within three years of qualification for health or behavioural reasons. This is referred to as premature retirement. The majority of premature retirements are due to behavioural problems in the dog. Whilst several studies have investigated traits indicative of guide dog qualification, there has been little research into predictors of partnership success post qualification. There is published research documenting how the end of a guide dog partnership is a distressing time for the owner. It has been suggested that owners of dogs that are retired prematurely are more at risk of experiencing distress during this time. The aims of this thesis were to explore the possible causes of an unsuccessful guide dog partnership and the impact premature retirement can have on guide dog owners (GDOs). Three separate studies were conducted to meet these aims. In Study One, semi-structured interviews were conducted with thirteen visually impaired people that had experienced premature retirement of a guide dog. The interviews explored various aspects of their relationship with their dog and how the retirement affected their lives. Thematic analysis identified three common themes across participants. The first theme, ‘Owner-Dog Relationship’ described the relationship the owners had with their dog, with a clear distinction between the working relationship and the dog as a pet. For many, although they enjoyed the relationship they had with their dog when not working together, difficulties arose when using the dog as a guide. The second theme was ‘Loss’, whereby participants described grieving the loss of the dog as a pet from their lives. The final theme was ‘well-being’, focusing on how the retirement affected participant’s emotional and physical health. Almost all participants reported a limitation in their mobility due to the retirement. Uncertainty and regret over the decision to have the dog retire was also felt by owners, impacting further on their well-being. For the second study, six of the partnerships from Study One, were investigated further through in-depth case studies. In each case, the puppy walker and re-homer were interviewed about the partnership and the dog. Standardised reports made by guide dog staff on the dog’s behaviour and the working partnership were collected. The owner, puppy walker and re-homer accounts, as well as the Guide Dogs staff reports were analysed and compared, to form conclusions on causes of retirement for each case. Cross case analysis was then used to highlight themes across cases. The findings highlighted the complex nature of the partnership, and the need for compatibility between the two in their work, as well as their social and home environments. When an incompatibility in any of these areas impacted the working relationship, this ultimately led to the breakdown of the partnership. Study Three explored some of the factors that may predict guide dog partnership success. Possible risk factors for unsuccessful partnerships were identified from observations of Guide Dogs, a literature review and the results of Studies One and Two. These risk factors were used to generate seven hypotheses on the predictability of guide dog partnership success. The hypotheses were tested on retrospective data from 4,504 guide dog partnerships that qualified between January 2009 and September 2014. Logistic regression analyses were used to test the effect of a range of variables on partnership success. GDOs that had previously experienced an unsuccessful partnership were more likely to have an unsuccessful partnership in the future. However, first time GDOs were more likely to have a successful partnership. This multidisciplinary research project highlights the importance of acknowledging both the owner and dog in human-dog dyads, the highly complex nature of the human-animal bond and factors that are specific to working partnerships with visually impaired owners. Both the working relationship, as well as the personal bond with the dog are of importance in the success of a guide dog partnership. These findings can help identify GDOs and partnerships that may be at risk of having a short working life, and may help with future matching of guide dog partnerships. These can also be applied to other assistance dogs and matching dogs from animal shelters to new homes. This is the first study to describe the impact of premature retirement on GDOs. It has highlighted the negative impact premature retirement can have on a GDO’s quality of life and the importance of providing appropriate emotional support.